THE IMPORTANCE OF TEACHING ENGLISH THROUGH THE USE OF LITERATURE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article provides information about the importance of teaching English through the use of literature and the methodology of teaching English.